Survey of attack graph based network security metric - Hao HU; Yuling LIU; Yuchen ZHANG; Hongqi ZHANG (网络与信息安全学报)
One of the main challenges of network security metrics is how to accurately identify the intrusion of the intruders exploiting the dependence between the vulnerabilities for threat propagation in the target network system as well as to quantify the potential impact on the network system.Because of its superior performance of visual display,the attack graph becomes one of the effective ways to solve the problem.Firstly,the concept,development and general metric models of security metrics were introduced.Secondly,the related researches with respect to attack graph construction,classification and application were discussed.Thirdly,a hierarchical framework for security metric using attack graph was proposed,and then existing methods of network security metric were summarized from three levels (key “point”,attack “line” and situation “plane”).Finally,the difficult issues and development trends for the current research were discussed.